B. Jasinowski as Methodologist of History of Philosophy and Philosopher of Culture - Jokubaitis, Alvydas (Problemos, 1991)
The ideas of Polish philosopher are analysed in the article. In B. Jasinowski’s works up to 1939 there exists the contradiction between conceptions of the methodology of history of philosophy and philosophy of culture. This is defined as the contradiction between psychologism of the methodology of history of philosophy and psychosociologism of philosophy of culture.